KEEFEKTIFAN PEMBELAJARAN SOSIAL KEARIFAN LOKAL BUDIDAYA UBI JALAR DI KALANGAN SUKU ARFAK KABUPATEN MANOKWARI - Matualage, Amestina (Sekolah Pascasarjana UGM, 2011)
The aimed of this research is to find a person who has become a figure respected by sweet potato farmers in Arfak during the social learning process of indigenous knowledge regarding sweet potato cultivation, understand the social learning process of indigenous knowledge regarding sweet potato cultivation, analyze the effectiveness of social learning of indigenous knowledgeregarding sweet potato cultivation, analyze the effectiveness of social learning of indigenous knowledge regarding sweet potato cultivation and analyze factors which affect the effectiveness of social learning of indigenous knowledge regarding sweet potato cultivation. The research was completed through descriptive analysis using a sample of 120 sweet potato farmers obtained randomly obtained from 2 districts and 4 villages in Manokwari regency. Results show that parents are the only figures in the social learning process of indigenous knowledge regarding sweet potato cultivation. The Arfak tribal farmers have high effectiveness, one affected by age and self-efficacy. The effect of self-efficacy on social learning effectiveness is reinforced by social support provided by parents.